Comparison of the performances of SALTCALC and LEACHMOD models for simulating the drainage and soil salinity conditions - SINGH, PRASHANT; MISHRA, ANIL KUMAR; JAISWAL, SMITA; KUMAR, LOVE; KUMAR, AMIT; KUMAR, AMIT (Journal of Soil and Water Conservation, 2023)
In Butana distributary of Western Yamuna Canal the twin problems of waterlogging and soil salinity have erupted due to over utilization of canal water; resulting into continuous rise of groundwater table that is predominantly caused by the impaired drainage, altered geo-hydrological conditions and poor irrigation management apart from other minor reasons (Singh et al., 2010). Extensive field investigations were carried out during May to November, 2016; to study the extent and severity of waterlogging and soil salinity. Soil samples were collected from 13 study points from four depths (0-30, 30-60 and 60-90, 90-120 cm) during May, June, August and November months. The calibrated values of the R2 and NSME were 0.83, 0.96, 0.93 and 0.91, 0.98, 0.91; respectively, for root zone salinity, transition zone salinity and water table depth from the SALTCALC model. The validated value of R2 and NSME were 0.85, 0.95, 0.92 and 0.89, 0.97, 0.96 for root zone salinity, transition zone salinity and water table depth meaning a very close fitting of observed and predicted parameters. Hence, SALTCALC model was used for scenario generation and prediction of future behaviour of the system